A history of chess - Giżycki, Jerzy 1919-2009 (<The>> Abbey Library, 1972)
A littlew history -- Chess in Britain -- Ramifications of chess -- Chess and mathematics -- Sport, science or art? -- Chess and machines -- Love and war at the chessboard -- Living chess -- Who and when? -- Chess in poetry and prose -- Chess curiosity box